Bidirectional flyback based isolated-port submodule differential power processing optimizer for photovoltaic applications - Chu, Guanying; Wen, Huiqing; Jiang, Lin; Hu, Yihua; Li, Xingshuo (Solar energy, 2017)
•Isolated-port differential power processing architecture at the submodule level is presented for partially shaded PV modules.•Bidirectional flyback topology was designed for each submodule with DCM and CCM modes for different mismatch conditions.•Voltage equalization with open-loop control was used for the submodule integrated converters.•The measured output power improvement with the DPP structure under severe mismatch condition was high up to 43.1%. Partial shading brings many serious problems in the solar photovoltaic system (SPV) such as the significant reduction in power harvest, hot spots, and the emergence of the multiple maximum power points (MPPs). This paper presents a bidirectional flyback converter (BFC) based isolated-port differential power processing (DPP) architecture at the submodule level. Bidirectional flyback converters (BFCs) are designed for submodules with both discontinuous condition mode (DCM) and continuous condition model (CCM) modes for light-load and heavy-load conditions to improve the efficiency. The voltage equalization with open-loop control is adopted for each BFC, this control method keeps the voltage in primary and secondary of the BFCs equal and it does not require additional voltage or current sensors. It’s simple, easy-to-implement and well suited for low-cost integrated hardware scheme. Both simulation and experimental results for an isolated-port DPP regulated 72-cells photovoltaic (PV) module under various partial shading scenarios were provided. It shows that this structure can distinctly mitigate the energy loss in a PV system, increase output power harvest, and achieve high efficiency under partial shading condition. The measured efficiency with the isolated-port DPP structure was 90.23% under severe shading condition. The measured output power improvement under severe mismatch condition was high up to 43.1%.